The Comparison of Using Think Pair Share (TPS) and Note Taking Pairs Techniques Toward Students’ Writing Ability In Term of Descriptive Text - Soifah Latifah (Faculty of Teacher Training and Education, Universitas Muhammadiyah Surakarta, 2022)
The objective of this research is to identify whether there is a significant difference between using Think Pair Share and Note-Taking Pairs techniques toward students' writing ability in terms of descriptive text at tenth grade of SMA Muhammadiyah 1 Metro academic year 2013/2014. There are four hypotheses in this research, those are; (1) The student's score of using the Think Pair Share technique is high seen by the result of the post-test, (2) The student's score of using the Note-Taking Pairs technique is high seen by the result of the post-test, (3) The student's score of students' writing ability in term of descriptive text high far seen by the result of the post-test, (4) The student's result of the comparison of using Think Pair Share and Note-Taking Pairs techniques toward student's writing ability in term of descriptive text is high seen by the result of the post-test. The subjects of the research were the tenth grade. The population of this research was the students in the tenth grade of SMA Muhammadiyah 1 Metro. The researcher took two classes. The first class is X3 as the experimental class. The second class is X4 as the control class. The samples of subjects were 40 students. The method of investigation is held through quantitative research. The design in this research is True Experimental design. In this experiment, the researcher applies Pre-Test Post-Test Control Group Design. The researcher uses cluster stratified random sampling as a technique sampling.